A controlled study of sexual function in men with cannabis use disorder: A brief report. (3rd September 2017) - Aldemir, Ebru; Akyel, Betul; Keskin Gokcelli, Duygu; Celikay, Hande; Altintoprak, A. Ender; Coskunol, Hakan
ABSTRACT: Background: Studies about the effects of cannabis on male sexual function have contradictory results. This contradiction is thought to depend on the subjective assessment of the patient or on the use of non-validated questionnaires. Aims: The objective of this study was to evaluate the sexual function of male patients with cannabis use disorder by a validated questionnaire and to compare them with a healthy control group. Methods: 47 male patients with cannabis use disorder and without any comorbid psychiatric disorders were included in this study. The education level and age of the patients were matched with 33 healthy male participants. In addition to the sociodemographic characteristics, the pattern of cannabis use and sexual life were also questioned. Sexual function was evaluated by International Index of Erectile Function. Results: The scores of erectile function and orgasmic function in the patient group were found significantly lower than the control group. Erectile dysfunction was significantly more frequently reported in the patient group than the control group. Sexual desire, intercourse satisfaction, and overall satisfaction scores did not differ significantly between groups. Conclusions: Our findings indicated that sexual function should be inquired in men with cannabis use disorder. These findings could be used in prevention studies focused on cannabis use disorder.